Methyl and ethyl ketone analogs of salicylaldehyde isonicotinoyl hydrazone: novel iron chelators with selective antiproliferative action - Macková, Eliška; Hrušková, Kateřina; Bendová, Petra; Vávrová, Anna; Jansová, Hana; Hašková, Pavlína; Kovaříková, Petra; Vávrová, Kateřina; Simůnek, Tomáš (Chemico-biological interactions, 2012)
Salicylaldehyde isonicotinoyl hydrazone (SIH) is a lipophilic, orally-active tridentate iron chelator providing both effective protection against various types of oxidative stress-induced cellular injury and anticancer action. However, the major limitation of SIH is represented by its labile hydrazone bond that makes it prone to plasma hydrolysis. Recently, nine new SIH analogues derived from aromatic ketones with improved hydrolytic stability were developed. Here we analyzed their antiproliferative potential in MCF-7 breast adenocarcinoma and HL-60 promyelocytic leukemia cell lines. Seven of the tested substances showed greater selectivity than the parent agent SIH towards the latter cancer cell lines compared to non-cancerous H9c2 cardiomyoblast-derived cells. The tested chelators induced a dose-dependent dissipation of the inner mitochondrial membrane potential, an induction of apoptosis as evidenced by Annexin V positivity or significant increases of activities of caspases 3, 7, 8 and 9 and cell cycle arrest. With the exception of nitro group-bearing NHAPI, the studies of iron complexes of the chelators confirmed the crucial role of iron in the mechanism of their antiproliferative action. Finally, all the assayed chelators inhibited the oxidation of ascorbate by iron ions indicating lack of redox activity of the chelator-iron complexes. In conclusion, this study identified several important design criteria for improvement of the antiproliferative selectivity of the aroylhydrazone iron chelators. Several of the novel compounds--in particular the ethylketone-derived HPPI, NHAPI and acetyl-substituted A2,4DHAPI--merit deeper investigation as promising potent and selective anticancer agents.
Keywords: screeningové testy protinádorových léčiv; hydrazony; Oxidation-Reduction; membránový potenciál mitochondrií; Ketones; Deferoxamine; protinádorové látky; Iron Chelating Agents; aldehydy; Humans; HL-60 buňky; Antineoplastic Agents; Hydrazones; kaspasy; chelátory železa; buněčný cyklus; oxidace-redukce; deferoxamin; Cell Cycle; Drug Screening Assays, Antitumor; Cell Line, Tumor; nádorové buněčné linie; Ascorbic Acid; apoptóza; kyselina askorbová; ketony; Caspases; HL-60 Cells; lidé; Aldehydes; Membrane Potential, Mitochondrial; Apoptosis